Efektivitas Pelaksanaan Pengembangan Kompetensi Aparatur Sipil Negara secara Daring (Studi Kasus di Pusat Pelatihan dan Pengembangan dan Kajian Hukum Administrasi Negara) - Fifi Ariani; Revita Rahim; Citra Permatasari (Puslatbang KHAN, 2022)
Competency development for the State Civil Apparatus (ASN) is an absolute thing to be fulfilled. The implementation of daring competency development towards competence fulfillment which aims to increase the competence of the State Civil Apparatus recently has become a phenomenon during the Covid-19 Pandemic. The purpose of this study is to determine the effectiveness of daring competency development in improving the competence of state civil servants, the impact of implementing competency development during the pandemic on increasing the competence of state civil servants and what are the roles of agencies in fulfilling the competence development of state civil servants. This research uses quantitative research methods spread questionnaire to collection data from employees via google form. The collected data will be processed and analyzed using quantitative methods where after the data is collected, classification will be carried out based in the need for further interpretation of the data to produce the required information. The collected data will be processed and analyzed using descriptive qualitative and quantitative descriptive methods where after the data has been collected, it will be classified based on the need for further interpretation of the data to produce the required information. The results expected from this research can provide an overview of the effectiveness of the implementation of employee competency development related to competency fulfillment and produce suggestions and input that can be formulated in making policy recommendations for the implementation of employee competency development.